The Effect of Outpatient Rehabilitation Program on the Quality of Life of Drug Abuse Patients in the National Narcotics Agency of North Sumatra Province in 2023 - Ivana, Cindy Lydia; Nababan, Donal; Martina, Siska Evi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Improving outpatient rehabilitation enhances the lives of those battling substance abuse. This study evaluates its impact at the National Narcotics Agency, North Sumatra. The study aims to assess outpatient rehabilitation's effectiveness on individuals with substance abuse history, focusing on physical health, psychological well-being, social support, and the environment. Using quantitative methodology with pre-post design, the entire patient population (n=54) was included. Research findings reveal significant and positive impacts of the rehabilitation program on physical health, psychological well-being, social support, and patient environmental conditions. Statistical analysis, with a significance level of (p < 0.001), confirms the remarkable success of the intervention, emphasizing the crucial role of the program in enhancing the overall quality of life for patients. This study delves into outpatient rehabilitation program effectiveness, highlighting the need for multidimensional support in the recovery journey.